FORMULASI DAN ANALISIS DESKRIPTIF KUANTITATIF RAISIN CAKE BERBASIS TEPUNG KOMPOSIT KACANG MERAH, KEDELAI, DAN JAGUNG (The Formulation and Quantitative Descriptive Analysis of Raisin Cake Based on Composites Flour: Redbean, Soybean, and Corn) - Astuti, Santi Dwi; Andarwulan, Nuri (Baristand Industri Banda Aceh, 2014)
Composite flour based on nuts and seeds can be formulated to obtainnutrient composition and bioactive compound as functional food ingredient. This study wasusing red bean and soybean flour as a source of protein that rich in dietary fiber andmicronutrients, and corn starch to improve the rheological properties of product. Theaimed of study was formulation of raisin cake based on composite flour rich in nutrients content and sensory analysis using quantitative descriptive analysis method. Compositeflour was consisting of red beans, soybeans and corn in the ratio of 65:25:10. Theproportion of composite flour as wheat flour substitution in raisin cake production were0%, 25%, 50%, 75%, and 100%. Quantitative descriptive analysis was performed using 10trained panelists. The results showed that product with composite flour up to 100% hassame intensity with control (raisin cake with 100% wheat flour) on sensory attributes i.e.elasticity, homogeneity, crust color, milky aroma and taste, raisin taste (sweet, acid,bitter), and fatty aftertaste. Raisin cake with composite flour substitution up to 50 % havethe same hardness and elasticity values with control. Raisin cake with 50% composite floursubstitution can be classified as functional food with claims as a good source of vitaminB6, and as very good source of protein, dietary fiber, calcium, magnesium, phosphorus,potassium, and vitamin C. Although product have the same preferences with control, itshave lower on vitamin B1 and vitamin B3 than control. Raisin cake with 50 % compositeflour was recommended to be consumed as a breakfast menu. Based on the nutritionadequation for general food, in each serving size (100g) of product was able to fulfill thedaily nutrition needs i.e. 16.48 % protein, 6.82 % total dietary fiber, 6.38 % calcium,10.46% magnesium, 17.96% phosphorus, 7.58% potassium, 7.36% zinc, 0.78% vitamin C,and 23.5% vitamin B12, respectively.